2005
DOI: 10.1016/j.cardiores.2005.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal KCNQ1 trafficking influences disease pathogenesis in hereditary long QT syndromes (LQT1)

Abstract: Our data revealed that channel trafficking may contribute to the pathogenesis of LQT1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 51 publications
5
69
1
Order By: Relevance
“…10). Recent evidence demonstrates that the normal trafficking to the plasma membrane of KCNQ1 is disrupted in channels bearing mutations associated with disease in nonhepatic tissue (47). The molecular identification of KCNQ1/KCNE3 in rat and human liver (27) and characterization of the signaling pathways involved in I KVol activation reported should permit discovery of ways in which to manipulate channel activity and ameliorate specific liver dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…10). Recent evidence demonstrates that the normal trafficking to the plasma membrane of KCNQ1 is disrupted in channels bearing mutations associated with disease in nonhepatic tissue (47). The molecular identification of KCNQ1/KCNE3 in rat and human liver (27) and characterization of the signaling pathways involved in I KVol activation reported should permit discovery of ways in which to manipulate channel activity and ameliorate specific liver dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…Pipette resistance, when filled with intracellular solution, was ϳ1.5-2.5 megaohms, and pipette capacitance was reduced by coating the tip with a parafilm oil suspension. Data were analyzed using Clampfit and Microcal Origin software (23,31). Current-voltage relationships were determined by normalizing the maximal current densities at the end of each pulse potential to cell capacitance (nA or pA/pF).…”
Section: Methodsmentioning
confidence: 99%
“…We introduced these alanine mutations singly or in combination into KCNQ1-GFP and co-expressed them with KCNE1 in CHO-K1 cells to replicate the molecular basis of the cardiac current. We have previously shown that KCNQ1-GFP behaves in an essentially identical fashion to KCNQ1 from a functional point of view (31). We used whole cell patching to measure and characterize the currents.…”
Section: What Are the Effects Of These Mutations On Channelmentioning
confidence: 99%
“…Several other cardiac ion channel subunit mutations cause impaired trafficking and have been linked with proarrhythmic syndromes including KCNQ1 (long QT1), 9 the majority of studied KCNH2 mutations (long QT2), 10 the potassium channel KCNJ2 (Andersen-Tawil), 11 SCN5A (CCD and Brugada syndrome), 12 and the hyperpolarization-activated cyclic nucleotide-gated channel 4 gene (sinus node disease). 13 In all of these examples, mutations result in trafficking-deficient proteins that fail to reach the plasma membrane, causing a loss of function.…”
Section: Article See P 374mentioning
confidence: 99%